The rise and fall of the Khalistan Movement: A chronology of events - Kataria, Shyamal (Advances in Social Sciences Research Journal, 2020)
The Khalistan Movement was an armed secessionist struggle led by the Sikhs of Punjab, in northern India. Perhaps the most haunting memories associated with the insurgency relate to the Indian Army’s brutal raid upon the ‘sanctum-sanctorum’ of the Sikh faith, the Golden Temple complex in Amritsar. While the support for Sikh political separatism pre-dates India’s independence, many scholars, albeit somewhat synthetically, attempting to place a fixed timeframe around the Khalistan movement tend to commence their chronology of events from 1981 and end them in 1993. This is largely because it was during this time period that Punjab endured a heightened level of Sikh militancy. What this article aims to do is to carefully detail the significant events that occurred during that period.